2024
DOI: 10.1038/s41526-024-00348-w
|View full text |Cite
|
Sign up to set email alerts
|

Modelling large scale artery haemodynamics from the heart to the eye in response to simulated microgravity

Harrison T. Caddy,
Lachlan J. Kelsey,
Louis P. Parker
et al.

Abstract: We investigated variations in haemodynamics in response to simulated microgravity across a semi-subject-specific three-dimensional (3D) continuous arterial network connecting the heart to the eye using computational fluid dynamics (CFD) simulations. Using this model we simulated pulsatile blood flow in an upright Earth gravity case and a simulated microgravity case. Under simulated microgravity, regional time-averaged wall shear stress (TAWSS) increased and oscillatory shear index (OSI) decreased in upper body… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…A similar relationship can be observed for the average OSI values, which for the rest are 0.076 for the 1G case and 0.063 for the 0G case. They are comparable to the results obtained by Caddy et al 76 . During moderate exercises, we get 0.013 (1G case) and 0.014 (0G case).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A similar relationship can be observed for the average OSI values, which for the rest are 0.076 for the 1G case and 0.063 for the 0G case. They are comparable to the results obtained by Caddy et al 76 . During moderate exercises, we get 0.013 (1G case) and 0.014 (0G case).…”
Section: Resultssupporting
confidence: 92%
“…Microgravity does not radically change OSI distribution at rest or during moderate exercise 76 , 77 . A healthy abdominal aorta is typically indicated by an OSI value of zero, which occurs in the primary oscillating blood flow.…”
Section: Resultsmentioning
confidence: 92%
“…Vascular damage is another factor of cardiovascular disease that has been observed during zero gravity conditions. To understand these outcomes, large scale artery dynamics were modeled in simulated microgravity, providing key insights on their modified mechanics ( Caddy et al, 2024 ).…”
Section: Advantages Of Microgravitymentioning
confidence: 99%
“…Venous thrombosis ( Auñón-Chancellor et al, 2020 ), anemia, and decreased hemoglobin concentration ( Trudel et al, 2020 ; Nicogossian, 2003 ) have all been observed in astronauts on the ISS. Further haemodynamic studies, such as Caddy et al’s, are necessary to resolve these issues ( Caddy et al, 2024 ).Alternatively, the hemoglobin degradation and hemolysis ( Trudel et al, 2022 ) can be utilized in tissue chips to evaluate mechanisms of hemolysis-causing diseases, such as malaria, or test possible therapies. Anemia also increases the susceptibility to infectious diseases like tuberculosis ( Gelaw et al, 2021 ), providing a more rigorous testing apparatus if implemented.…”
Section: Advantages Of Microgravitymentioning
confidence: 99%